2012
DOI: 10.1177/0011392112438335
|View full text |Cite
|
Sign up to set email alerts
|

Integrating health and social care: Interprofessional relations of multidisciplinary teams in Italy

Abstract: Integrating health and social care has been a major objective of recent policy reforms in Italy. Integration has been implemented on three levels, namely institutional, organizational and professional. At the professional level multiprofessional teams have been created or adapted (if existing) in several areas, including among others, care of the elderly, the disabled and the addicted. This article discusses the findings of an empirical study based on 57 interviews with managers and members of community-based,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 47 publications
2
33
0
2
Order By: Relevance
“…As the authors put it: ‘The evolution of the discipline and the trend towards a tailored therapy suggest that health economics is not the end of clinical freedom but the start of it’ [22], p. 1; see also [23]. Tousijn [24], p. 529. in an Italian case study, also found that doctors ‘create their own managerial procedures’ rather ‘adapting’ or ‘modifying’ existing managerial procedures or ‘circumventing them’.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the authors put it: ‘The evolution of the discipline and the trend towards a tailored therapy suggest that health economics is not the end of clinical freedom but the start of it’ [22], p. 1; see also [23]. Tousijn [24], p. 529. in an Italian case study, also found that doctors ‘create their own managerial procedures’ rather ‘adapting’ or ‘modifying’ existing managerial procedures or ‘circumventing them’.…”
Section: Introductionmentioning
confidence: 99%
“…Such new forms have been described variably as: ‘hybridisation’ [36], p. 761 or ‘organized professionalism…calling for multi-professional acts’ [37], p. 1360. ‘diversity of professionalism’ and flexibility between exclusionary and more ‘inclusive’ patterns [21], p. 221; ‘compatibility’ of different modes [28], p. 634 and ‘community professionalism’, as suggested by Tousijn [24], p. 533 with reference to Adler et al [38]. Although the ‘labels’ differ, these approaches make much the same plea for overcoming the managerialism-professionalism dichotomy.…”
Section: Introductionmentioning
confidence: 99%
“…The dominance of North-American and Anglo-Saxon approaches in the sociology of professions has led to a situation where the model of 'liberal societies' that underpins the regulatory architecture of the state-profession relationships in these countries, has informed the study of professions (Abbott 1988;Freidson 2001;Larson 1977;Light 2010). Hence, in many European welfare states public responsibility for social services enjoys higher currency and the state-profession relationships has taken different forms than in the liberal welfare states, as the more integrated models in the Scandinavian countries and the corporatist arrangements in continental European countries highlight, such as for instance Germany (Bertilsson 1990;Kuhlmann and Burau 2008;Tousijn 2012). And to make things even more complicated, transformations in the professions may also play out differently within different parts of the AngloAmerican world, as McDonald (2012) reveals in her comparative analysis of medical performance in England and California.…”
Section: Rethinking Professions: the Blind Spots Of A 'Northern Lens'mentioning
confidence: 99%
“…In other words, managerialism and professionalism act as 'twin forces' rather than contradicting logics, as described with respect to the developments in European hospital governance (Kuhlmann et al 2011: 723;Reay and Hinings 2009). These developments are accompanied by new demands for changing the skill mix and shifting tasks in the health professional workforce and an overall need for more integrated care, teamwork and improved coordination between the health professional groups and the different sectors of hospital care and primary care Tousijn 2012).…”
Section: The Challenges Of New Governance and Public Sector Managementmentioning
confidence: 99%
“…Studies have also moved from a specific concern with medical aspects of health systems to a broader understanding of health policy and services as studies of public health, mental healthcare and long-term care testify (see, for instance, Blank and Burau, 2010). This aspect of diversity is also strongly represented in this monograph issue, where Taylor et al (2012) examine local approaches to healthcare prevention, Tousijn (2012) analyses the integration of health and social care through multidisciplinary teams and Matsushige et al (2012) place the focus on integrated home care.…”
Section: Bringing Diversity Into Comparative Health Studiesmentioning
confidence: 99%